Customer intimacy analytics: Leveraging operational data to assess customer knowledge and relationships and to measure their business impact - François Habryn (KIT Scientific Publishing, 2012)
The ability to capture customer needs and to tailor the provided solutions accordingly, also defined as customer intimacy, has become a significant success factor in the B2B space - in particular for increasingly "servitizing" businesses. This book elaborates on the solution CI Analytics to assess and monitor the impact of customer intimacy strategies by leveraging business analytics and social network analysis technology. This solution thereby effectively complements existing CRM solutions.
urn:nbn:de:0072-281596
Keywords: 650; Customer Intimacy; Business Analytics; Social Networks; Services; Strategy; Beziehungsmarketing; Management-Informationssystem